Relatório final do estágio curricular obrigatório do curso de medicina veterinária, realizado junto ao Instituto de Ciências Biomédicas (ICB-USP), São Paulo, SP, e ao Instituto René Rachou (Fiocruz Minas), Belo Horizonte, MG. Assunto de interesse: Levantamento ecoepidemiológico de Leishmania spp. no Brasil. - Arantes, Paulo Vitor Cadina [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O presente trabalho engloba o relatório final de estágio curricular, apresentando a descrição das entidades de estágio, descrição das atividades desenvolvidas, discussão e considerações finais. Além disso, apresenta um levantamento ecoepidemiológico das leishmanioses no Brasil, bem como uma revisão bibliográfica a respeito do referido agente.

The present work encompasses the final report of the required curricular internship, presenting the description of the internship entities, description of the developed activities, discussion and final considerations. In addition, it presents an ecoepidemiological survey of leishmaniasis in Brazil, as well as a bibliographical review about the referred agent.
Final report of the required curricular internship of the veterinary medicine course, carried out at the Institute of Biomedical Sciences (ICB-USP), São Paulo, SP, and the René Rachou Institute (Fiocruz Minas), Belo Horizonte, MG. Subject of interest: Ecoepidemiological survey of Leishmania spp. in Brazil.
Keywords: Parasitologia; Epidemiologia; Zoonoses